Pengaruh Dosis Pupuk Organik Cair Urine Kelinci Terhadap Pertumbuhan dan Hasil Tanaman Dua Varietas Bayam Merah (Amaranthus Tricolor L.): Pengaruh Dosis Pupuk Organik Cair Urine Kelinci Terhadap Pertumbuhan dan Hasil Tanaman Dua Varietas Bayam Merah (Amaranthus Tricolor L.) - Putri Pamungkas Septianingrum; Endang Suprapti; Tyas Soemarah Koernia D; Wiyono; Siti Mardhika Sari (JURNAL ILMIAH AGRINECA, 2026)
The purpose of this study was to determine the effect of adding a dose of liquid organic fertilizer from rabbit urine on plant height, number of leaves, total fresh weight of plants, dry weight of stover, consumption weight, fresh roots and dry roots of plants on red spinach varieties. The research was conducted from November to December 2025 at KBTPH Tohudan, Colomadu, Karanganyar. The method used is a Completely Randomized Design (CRD) with two treatment factors and three replications. The first factor was addition of liquid organic fertilizer from rabbit urine dosage per plant (D1: 0 ml; D2: 50 ml; D2: 100 ml; D3: 150 ml; D4: 200 ml; D5: 250 ml). 2. The second was types of red spinach varieties (V1: Mira Variety; V2: Red Baret Variety). The application of 250 ml/plant of liquid organic fertilizer from rabbit urine and red spinach variety Mira resulted in the best average growth and yield of the red spinach plant.